The Influence of Buyer Service Behavior As Partners on Customer Satisfaction By Kia Marketing Consultants - Antonius Agustino; Irwan Tanamas; Alfred Inkiriwang; Marisi Pakpahan; Ratnawati Prayogi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Competition in the business world has become increasingly intense, compelling business actors to establish competitive advantages in order to survive and boost sales. Among the strategies that can be implemented is to enhance service quality while offering competitive prices. This study aims to analyze the services provided to buyers as partners by KIA consultants and to investigate the impact of these services on customer satisfaction. The method employed is quantitative descriptive, utilizing a survey technique to sample the population, with a questionnaire as the primary tool for data collection using a Likert scale. The targeted population consists of buyers or visitors at KIA dealerships located in Bogor, Jakarta, and several other areas. The sample in this study comprises 90 respondents. The results indicate that the service quality variable has a significant impact on customer satisfaction, with a t-test significance value of 0.000, which is less than 0.05. Conversely, the price variable does not influence customer satisfaction, with a t-test significance value of 0.298, which is greater than 0.05. Additionally, both service quality and price collectively affect customer satisfaction, with an F-test significance value of 0.000, which is also less than 0.05.